Economic Development in Eastern Germany: History, Expectations, and Public Policy - Thomas M. Steger; Andreas Schäfer (Verein für Socialpolitik, 2010)
Motivated by the process of economic development in Eastern Germany since the German reunification we set up a dynamic macroeconomic model of a small open economy where both capital and labor are mobile and there are increasing returns to scale at the aggregate level. The model features multiple equilibria and (local and global) indeterminacy. Expectations matter for resulting equilibrium dynamics, implying that good or bad moods are crucial for the process of economic development. We argue that this simple model is in line with the major stylized facts. The model is also instructive when it comes to better understanding the consequences of macroeconomic supply side policy and the pattern of East-West convergence.
Keywords: E60; H20; O40; 330; increasing returns to scale; capital mobility; migration; multiple equilibria; indeterminacy; history vs. expectations; economic policy